Sleep Duration and Quality: Impact on Lifestyle Behaviors and Cardiometabolic Health. Issue 18 (1st November 2016) - St-Onge, Marie-Pierre; Grandner, Michael A.; Brown, Devin; Conroy, Molly B.; Jean-Louis, Girardin; Coons, Michael; Bhatt, Deepak L.
Abstract : Sleep is increasingly recognized as an important lifestyle contributor to health. However, this has not always been the case, and an increasing number of Americans choose to curtail sleep in favor of other social, leisure, or work-related activities. This has resulted in a decline in average sleep duration over time. Sleep duration, mostly short sleep, and sleep disorders have emerged as being related to adverse cardiometabolic risk, including obesity, hypertension, type 2 diabetes mellitus, and cardiovascular disease. Here, we review the evidence relating sleep duration and sleep disorders to cardiometabolic risk and call for health organizations to include evidence-based sleep recommendations in their guidelines for optimal health.